Amplified characterization of the Innovahubs: Context-specific analysis and mapping of the Innovahub influence areas in Guatemala and Honduras - Martínez, Jesús David; Borrayo, Andrea; García Masse, Louis N.; Loon, Jelle van (Bioversity International and the International Center for Tropical Agriculture, 2023)
The year 2023 marked another significant milestone in the ongoing effort of the Resilient AgriLAC initiative to establish and strengthen the Innovahubs in Central America. Following the exercises held in 2022 to map and understand the geomorphology and viability of crops in the areas of intervention in Guatemala and Honduras, this year the work intensified with a more thematic characterization of the Innovahubs' zones of influence. The 2023 report is structured with the presentation of 2 context-specific analyses on nutrition and market access for rural communities, and the finalization of the technical information of the Innovahubs in Mexico In Chiquimula, Guatemala, a study on diet quality highlighted the crucial role of nutrition for human wellbeing and agricultural outcomes, setting a precedent for similar studies in other regions. Concurrently, a comprehensive value chain analysis in Guatemala and Honduras pinpointed market access opportunities for producers, alongside potential vulnerabilities threatening Innovahubs' resilience. Additionally, a standout contribution was the infographic guide "Innovation and Resilience - A look at the impact of hubs in Mexico," unveiled at the PCCMCA forum in Antigua, Guatemala, offering a concise overview of the progress and challenges faced by Mexico's Innovahubs. Through these integrated efforts, Resilient AgriLAC reaffirms its commitment to the integrated development of Innovahubs in the region, facilitating people-centered innovation and the creation of resilient food systems in Latin America.